The SAGE handbook of multilevel modeling - Scott, Marc A., 1974-; Simonoff, Jeffrey S.; Marx, Brian D., 1960-; Sage eBooks (Los Angeles : SAGE, 2013)
This handbook establishes the connections in multilevel modelling, bringing together leading experts from around the world to provide a roadmap for applied researchers linking theory and practice, as well as an arsenal of state-of-the-art tools. In so doing, it forges vital connections in best-practice in the field that cross traditional disciplinary divides.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Multilevel models (Statistics); Electronic books